Multiple Sclerosis and Neuroinflammation: The Overview of Current and Prospective Therapies - Bjelobaba, Ivana; Savic, Danijela; Lavrnja, Irena (Current Pharmaceutical Design, 2017)
Persistent neuroinflammation is now recognized as a chief pathological component of practically all neurodegenerative diseases. Neuroinflammation in the central nervous system (CNS), is accompanied with immune responses of glial cells. Glial cells respond to pathological stimuli through antigen presentation, and cytokine and chemokine signaling. Therefore, limiting CNS inflammation represents prospective therapeutic approach in diseases like Alzheimer’s, amyotrophic lateral sclerosis, Parkinson’s, ischemia, various psychiatric disorders and Multiple sclerosis (MS). As a complex disease, MS is characterized by neuroinflamation, demyelination and sequential axonal loss. Due to unknown etiology and the heterogeneous presentation of the disease, MS is hard to treat and the search for potential therapeutics is wide and meticulous. However, finding a proper antineuroinflammatory drug may bring an advance in selecting novel treatment regimens of ample of neurodegenerative diseases and neurological disorders. The present review gives the overview of the existing and potential therapies in MS, aimed to modulate neuroinflammation and ensure neuroprotection.
Keywords: therapies